2012
DOI: 10.1002/anie.201206468
|View full text |Cite
|
Sign up to set email alerts
|

A Thermally Stable Gold(III) Hydride: Synthesis, Reactivity, and Reductive Condensation as a Route to Gold(II) Complexes

Abstract: Going for gold: The first thermally stable gold(III) hydride [(C N C)*AuH] is presented. It undergoes regioselective insertions with allenes to give gold(III) vinyl complexes, and reductive condensation with [(C N C)*AuOH] to the air-stable Au(II) product, [(C N C)*(2)Au(2)], with a short nonbridged gold-gold bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 94 publications
3
97
0
5
Order By: Relevance
“…We found recently that C^N^C pincer ligands based on the dianionic 2,6-diphenylpyridine framework are capable of stabilizing a number of novel gold(III) compound types 32,33 , including the first examples of gold(III) hydrides and olefin complexes 34,35 . Given the importance of oxygen ligands in oxidations as well as water cleavage reactions, we decided to explore the reactivity of such gold(III) pincer complexes towards oxygen ligands, including possible Au-O2Au-H interconversions.…”
mentioning
confidence: 99%
“…We found recently that C^N^C pincer ligands based on the dianionic 2,6-diphenylpyridine framework are capable of stabilizing a number of novel gold(III) compound types 32,33 , including the first examples of gold(III) hydrides and olefin complexes 34,35 . Given the importance of oxygen ligands in oxidations as well as water cleavage reactions, we decided to explore the reactivity of such gold(III) pincer complexes towards oxygen ligands, including possible Au-O2Au-H interconversions.…”
mentioning
confidence: 99%
“…[5] Dieser Pfad wird besonders durch die Au-Au-Bindung potentiell verbrückende Liganden, wie SO 4 2À (Au-Au2 .490 ), [CH 2 PR 2 CH 2 ] À oder [S 2 CNR 2 ] À (2.550-2.694 ), bevorzugt. [14] Die homolytische Bindungsspaltung in einkernige Fragmente Au II (C^N^C) bençtigt 198 AE 1kJmol À1 . [13] Kürzlich verwirklichten Bochmann et al im Komplex (C^N^C)Au II -Au II -(C^N^C) mit einem doppelt cyclometallierten 2,6-Bis(4'-tertbutylphenyl)pyridin-Liganden eine weitere unverbrückte, kurze Au-Au-Bindung (Au-Au2 .4941 )( Schema 1).…”
Section: Einführungunclassified
“…Bochmann et al [122] reported on a gold(III) hydride pincer complex that is unreactive towards several alkynes and alkenes, but undergoes insertion reactions with allenes, yielding regioselectively Au(III)vinyl complexes (Scheme 3.46).…”
Section: Insertion Reactions In Gold Chemistrymentioning
confidence: 99%